A novel compressed air energy storage (CAES) system combined with pre-cooler and using low grade waste heat as heat source. (15th July 2017) - Chen, Long-Xiang; Hu, Peng; Sheng, Chun-Chen; Xie, Mei-Na
Abstract: Decreasing fuel consumption in compressed air energy storage (CAES) system is a general trend for conserving energy and protecting the environment. Waste heat recovery is an interesting technology to compact energy storage system. However, CAES system has a low thermal efficiency when using low grade waste heat as heat source directly. In this paper, an integrated energy system consisting of a CAES system and a precooling system (PC-CAES) is proposed to decrease the energy consumption of compression train in the charging process, and enhance the round trip efficiency (RTE) of the system. Air conditioner is utilized as pre-cooler to precool the inlet air of compressor and five refrigerants are investigated. The thermodynamic analysis is performed by using steady-state mathematical model and thermodynamic laws. The calculation results show that the RTE of the proposed PC-CAES system is improved by more than 3% than that of the conventional CAES system and more economical than CAES with additional compression stages. Meanwhile, a parametric analysis is also carried out to evaluate the effects of several key parameters on the system performance of two CAES systems. Highlights: A novel CAES system combined with pre-cooler is introduced. Proposed PC-CAES is more compact than A-CAES by using free waste heat. Air conditioner is utilized as pre-cooler to precool the inlet air of compressor. Efficiency improvement is achieved via cool down the compressor inlet air temperature.